Effect of cultivar and inoculant on yields of faba beans (Vicia faba minor) and subsequent spring wheat (Triticum aestivum) under Scandinavian cropping conditions - Fogelberg, Fredrik; Östlund, Johanna; Myrbeck, Åsa (Frontiers in Agronomy, 2023)
Inoculation of legumes is generally considered to increase yield and lower the need of nitrogen (N)-fertilization, especially in semi-arid regions and on sandy soils. It has not been clear if inoculation with Rhizobium sp. in cropping of faba beans (Vicia faba minor) under Swedish conditions would improve yield and protein content. In 2015-2016 three faba bean cultivars and two strains of Rhizobium were studied in field trials in Central Sweden, including analyses of N fixation capacities using 15N-abundance. The study did not show any effects of inoculation of Rhizobium on yield or protein content of faba beans or subsequent spring wheat yields. Yields of faba beans varied between cultivars but were not connected to inoculation. 15N-abundance was influenced by rhizobium. The study cannot support the opinion that inoculation generally is beneficial for improved outcome of faba bean cropping under Scandinavian field conditions. No residual effect of inoculation on subsequent spring wheat yield was found.